CURCUMA DOMESTICA AND MORINGA OLEIFERA EXTRACT GEL AS AN ALTERNATIVE FOR GINGIVAL BRIGHTENING: A PILOT STUDY - Pratiwi, Devy Anugraeni; Bilqis, Tsuraya; Fitriyani, Rahma Dwi; Dewi, Elya Mardhania Tiara; Rismawati, Nadya; Sukmawati, Ayuda Nur (Indonesian Journal of Dentistry, 2025)
Background: Gingival hyperpigmentation can occur in active smokers with high frequency. The current treatment is surgical. Therefore, researchers found a new breakthrough by creating a minimally extensive treatment, namely gel preparations. Combination of turmeric (Curcuma domestica) and moringa leaf (Moringa oleifera) extract that has the potential as a tyrosinase enzyme inhibitor. The extract will be made in a gel preparation. This study aims to determine the most optimal concentration of the gel. Method: This study used an experimental method. The gel preparation was made with various concentrations of turmeric extract and moringa leaf extract, namely F1 0.1%: 2%, F2 0.5%: 4% and F3 0.9%: 6%. Followed by testing the physical and chemical properties. Chemical properties in the form of pH, physical properties in the form of organoleptic, homogeneity, adhesiveness and spreadability by measuring the diameter of TB (No Load), B50 (Load 50 g), B100 (Load 100 g) and B150 (Load 150 g). Results: The results showed that F1, F2 and F3 were homogeneous with dark brown color, distinctive smell of moringa leaves and increasingly dilute form with each additional concentration with pH (F1) 7.99, (F2) 7.71 and (F3) 7.58. The spreadability of gel preparation F1 (TB) 2.7, (B50) 2.8, (B100) 2.9, (B150) 3.1; F2 (TB) 2.8, (B50) 3.1, (B100) 3.3, (B150) 3.5 and F3 (TB) 4.2, (B50) 4.6, (B100) 4.7, (B150) 5.1 based on these observations it is known that F3 meets the criteria for spreadability at a load of 150 gr. Conclusion: Based on this study, it can be concluded that F3 gel, a combination of turmeric extract and moringa leaf extract, has the most optimal formula because it almost meets all the requirements for gel preparations.